The Twenty-Ninth Day: Surviving a Grizzly Attack in the Canadian Tundra (2023-03-02) - Messenger, Alex; University of Minnesota Duluth. Royal D. Alworth, Jr. Institute for International Studies (2023)
Thursday, March 2, 2023; 12:00 pm; UMD Library Rotunda; Presented by Alex Messenger, Communication Specialist, UMD; The Twenty-Ninth Day is available for purchase at the UMD stores and will be sold at the event. Royal D. Alworth, Jr. Institute for International Studies